INFLAMMATION MARKERS ANALYSIS AMONG CHILDREN, SUFFERING FROM ACUTE BRONCHITIS AGAINST FENSPIRIDE BASED TREATMENT - N.A. Il'enkova; O.V. Alekseeva; V.V. Chikunov ("Paediatrician" Publishers LLC, 2007)
The authors stud the clinical efficiency of fenspiride (Erespal) among children (n = 46), suffering from acute bronchitis. It was shown that fenspiride reduced the cough duration and conduced to faster improvement of the patients' health. Besides, fenspiride application was accompanied by the reduction of the anti-inflammatory cytokines both in the blood serum and condensate of expired air.Key words: bronchitis, fenspiride, cytokines, condensate of expired air, children.